Judicial Accountability For Control on Freedom of Speech With Respect to People’S Responsibility: Exploring the Role of Judiciary in Safeguarding Freedom of Speech (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In a democracy, the role of judiciary is crucial.  Judiciary is a faithful keeper of the constitutional assurances. An independent and impartial judiciary can make the legal system vibrant. Our Indian judiciary can be regarded as a creative judiciary. Credibility of judicial process ultimately depends on the manner of doing administration of justice. Justice K. Subba Rao explains the function of the judiciary as thus: